2009
DOI: 10.1002/jat.1451
|View full text |Cite
|
Sign up to set email alerts
|

Shift of oxidants and antioxidants levels in rats as a reaction to exposure to sulfur mustard

Abstract: Antixodants as well as oxidants levels were investigated in plasma of rats exposed to sulfur mustard in doses of 0 (control), 5, 20 and 80 mg kg(-1) body weight. Cyclic voltammetry performed on screen-printed strips with platinum working electrode used as a tool for assaying oxidant and antioxidant levels. We found significant shifts in both examined analytes. A dose of sulfur mustard of 5 mg kg(-1) body weight caused only a small change in oxidant and antioxidant levels when compared with the control group. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Oxidative stress is one of the most studied mechanisms in SM-induced skin injury (Han et al , 2004; Pal et al , 2009; Pohanka and Stetina, 2009; Laskin et al , 2010). Our previous studies have shown that oxidative stress plays an important role in the activation of complex signaling pathways that lead to CEES-caused skin injury (Pal et al , 2009; Tewari-Singh et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is one of the most studied mechanisms in SM-induced skin injury (Han et al , 2004; Pal et al , 2009; Pohanka and Stetina, 2009; Laskin et al , 2010). Our previous studies have shown that oxidative stress plays an important role in the activation of complex signaling pathways that lead to CEES-caused skin injury (Pal et al , 2009; Tewari-Singh et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] At the first step of the defense system against oxidative stress, superoxide dismutase catalyzes dismutation of the superoxide anion into H 2 O 2 . At the second step of the antioxidant defense system, glutathione peroxidase and catalase independently degrade H 2 O 2 to water.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previous experiments, equimolar doses of oximes were administered into the animals. All the drugs were selected from previous studies as being potent AChE reactivators in vitro; obidoxime, trimedoxime and HI-6 are currently available in many countries including NATO members [13][14][15]. Their potency to reactivate AChE was evaluated by in vitro studies and seemed to be sufficient [16].…”
Section: Resultsmentioning
confidence: 99%
“…An increase of LMWA is associated with stress that may arise in non-pathological conditions [21]. Healthy organisms are able to protect themselves even when they are exposed to high doses of toxic compounds such as sulphur mustard [13]. Oxidative stress arises when an organism is insufficiently protected and this can occur shortly after a toxicity burden [22,23].…”
Section: Discussionmentioning
confidence: 99%